Candy F.

asked • 07/06/16

Quadratic formulas


2 Answers By Expert Tutors


Hassan O. answered • 07/06/16

3 (1)

Mathematics Graduate

Andrew M.

Once Hassan put the equation into standard form of
4t2-8t+3 = 0 the factoring was done by grouping.
Take the coefficient of the square term (4) and multiply
it by the constant (3)... 4(3) =12
Look for factors of this product that add to the coefficient
of the middle term (-8)... Note that (-6)(-2)=12 and -6-2=-8
Replace -8t with -2t-6t in the equation
then factor.
4t2 - 8t + 3 = 0
4t2 - 2t - 6t + 3 = 0
Factor 2t from 1st 2 terms and -3 from last 2 terms
2t(2t-1)-3(2t-1) = 0
This gives us the factor form of:
From there the solution, as given by Hassan O. comes to
t = 3/2 or t = 1/2


Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.


Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.